Tuntematonta sotilasta ja jatkosotaa mahdoton erottaa toisistaan - Rami Mähkä (Finland, 2022)
The newspaper column discusses public responses to the recent Finnish film Tuntematon sotilas (Unknown Soldier, dir. Aku Louhimies, released October 2017), based on the classic novel by the same name by Väinö Linna (1954), and filmed twice before (1955 and 1985). The novel and Edvin Laine's film (1955) are one of the most important Finnish fictions. My argument is that the instant outcry of the new film version happened - before anyone had seen it; the mere idea of a remake caused the reaction - because of political confrontations of late, and that Tuntematon sotilas and the war in which it is set, the Continuation War (1941-44), can be only theoretically separated from one another in the Finnish ideas and conceptions of the war.